Differential Impact of LPG-and PG-Deficient Leishmania major Mutants on the Immune Response of Human Dendritic Cells. - Michelle A Favila; Nicholas S Geraci; Asha Jayakumar; Suzanne Hickerson; Janet Mostrom; Salvatore J Turco; Stephen M Beverley; Mary Ann McDowell (PLoS Neglected Tropical Diseases, 2015)
BACKGROUND:Leishmania major infection induces robust interleukin-12 (IL12) production in human dendritic cells (hDC), ultimately resulting in Th1-mediated immunity and clinical resolution. The surface of Leishmania parasites is covered in a dense glycocalyx consisting of primarily lipophosphoglycan (LPG) and other phosphoglycan-containing molecules (PGs), making these glycoconjugates the likely pathogen-associated molecular patterns (PAMPS) responsible for IL12 induction. METHODOLOGY/PRINCIPAL FINDINGS:Here we explored the role of parasite glycoconjugates on the hDC IL12 response by generating L. major Friedlin V1 mutants defective in LPG alone, (FV1 lpg1-), or generally deficient for all PGs, (FV1 lpg2-). Infection with metacyclic, infective stage, L. major or purified LPG induced high levels of IL12B subunit gene transcripts in hDCs, which was abrogated with FV1 lpg1- infections. In contrast, hDC infections with FV1 lpg2- displayed increased IL12B expression, suggesting other PG-related/LPG2 dependent molecules may act to dampen the immune response. Global transcriptional profiling comparing WT, FV1 lpg1-, FV1 lpg2- infections revealed that FV1 lpg1- mutants entered hDCs in a silent fashion as indicated by repression of gene expression. Transcription factor binding site analysis suggests that LPG recognition by hDCs induces IL-12 in a signaling cascade resulting in Nuclear Factor κ B (NFκB) and Interferon Regulatory Factor (IRF) mediated transcription. CONCLUSIONS/SIGNIFICANCE:These data suggest that L. major LPG is a major PAMP recognized by hDC to induce IL12-mediated protective immunity and that there is a complex interplay between PG-baring Leishmania surface glycoconjugates that result in modulation of host cellular IL12.